From discovering to delivering: A critical reflection on eco-feedback, application design, and participatory research in the United Kingdom. (October 2020) - Chalal, Moulay Larbi; Medjdoub, Benachir; Bull, Richard; Shrahily, Raid; Bezai, Nacer; Cumberbatch, Miranda
Abstract: The area of Eco-Feedback has received significant attention in recent years. Whilst there have been increasing calls to move 'beyond feedback' and consider the wider social, organisational and cultural context that feedback sits within, the involvement of community members in the design process of eco-feedback applications, known as co-design, has been limited. This study addresses that research gap through working collaboratively with community members to develop an accessible eco-feedback interface. First, we conducted an online survey questionnaire with 151 respondents with distinct socio-economic characteristics and environmental knowledge to get insights into their preferences about different aspects of the eco-feedback interface. Secondly, based on the survey findings, 20 community members living in Nottingham, UK, worked collaboratively to develop interface design proposals. Finally, the design of the eco-feedback interface was finalised based on the community interface prototypes and suggestions. The developed interface contains multiple information panels with options for expanding to gain deeper levels of information and a community space allowing for community interactions and sharing of information and actions. This research sheds new light on the challenges of utilising co-design principles to build eco-feedback interfaces. Specifically, we highlight the potential for interactions between community members during the design stages to allow for the generation of innovative ideas (e.g. Integration of third-party applications) moving the interface beyond feedback leading to greater adoption and energy savings.